The best trigonometric approximations and the Kolmogorov diameters of the Besov classes of functions of many variables - Romanyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The order estimates for the best trigonometric approximations and the Kolmogorov diameters of the classes B^r_p, θ of functions of many variables in the space L_q are obtained for certain values of the parameters p, q.